Activity coefficients of hydrocarbons at infinite dilution in di-n-octyltin dichloride: comparison with results obtained in other alkyltin solvents - Nardillo, Ángel Miguel (1996)
The gas chromatographic method was employed to measure the infinite dilution activity coefficients of twenty-eight hydrocarbons of different types in di-n-octyltin dichloride between 50 and 80°C, and of seven branched alkanes in tri-n-octyltin chloride between 40 and 60°C. A comparison is made between the results obtained for all the solutes in both solvents and in tetra-n-octyltin.